Bacteriological Quality of Locally Prepared Fresh Fruit Juice Sold in Juice Houses of Eastern Ethiopia - Dechasa Adare Mengistu; Yohannes Mulugeta; Dinku Mekbib; Negga Baraki; Tesfaye Gobena (SAGE Publishing, 2022)
Background: Currently, fresh fruit juices are widely consumed as a drink worldwide due to their nutritional values and health benefits. Fresh fruit juices are an important source of nutrients, vitamins, and fibers that are important for human health. Fruit juices are nutritious and perishable food that can serve as an ideal medium for the growth and multiplication of pathogenic microorganisms. Therefore, this study aimed to determine the bacteriological quality of locally prepared fresh fruit juices sold in juice houses of eastern Ethiopia from 4 April to 12 June 2020. Methods: A cross-sectional study was used that included administrative questionnaires and laboratory-based investigations. A total of 78 fruit juice samples that include mango, avocado, papaya, and mixed juices were collected aseptically from the juice houses. The most probable number method was used to determine the total coliform, fecal coliform and Escherichia coli . The pour plate count method was used to determine the total viable bacteria count. Finally, data were analyzed using descriptive statistical tests that included analysis of variance, Chi-square and Fisher's exact tests. A P -value of .05 was considered as a cut-off point for statistical significance. Results: Among the 78 juice samples analyzed, 85.9% of the samples had total viable bacterial count, 64.1% had total coliform count, 60.3% had fecal coliform, and 33.3% of the samples had Escherichia coli higher than the maximum permitted level of Gulf standard 2000. The study found a significant association between bacterial contamination and educational status (χ 2  = 31.663), training in food hygiene and safety (χ 2  = 23.04), method of fruit preservation (χ 2  = 17.98), place to keep the juice (χ 2  = 13.7), action done with the juice gone bad (χ 2  = 12.78), frequency of cleaning materials used to keep the juice (χ 2  = 12.78), type of dish washing (χ 2  = 19.75), availability of hand washing equipment (χ 2  = 12.78), and types of waste receptacles (χ 2  = 26.25) ( P -value <.05) (Table 5). Conclusion: In general, majority of fruit juice samples were contaminated with one or more different bacteria species higher than the maximum permitted level. Furthermore, the study found the association between bacterial contamination and other variables such as hygienic and safety conditions. Therefore, the implementation of adequate hygiene and safety practices is very important to prevent the consumption of contaminated fruit juices, which leads to foodborne illness.